DESIGN OF A CAPACITIVE SENSING SYSTEM FOR MEASUREMENT OF WATER CONTENT IN CRUDE OIL - ASLAM, MUHAMMAD ZUBAIR (2014)
During crude oil exploration, transportation and refining process, the measurement of water content is always a challenging widespread problem for researchers. Some conventional measurement methods are researched in last decades but those methods are laborious, less accurate and required special experimental preparations for a single measurement. In this work, a capacitive sensing system for measurement of water content in crude oil is presented. The proposed system is mainly divided into two phases. In first phase, designing of capacitive sensor is performed for our particular application of water content measurement in crude oil. The relation between water concentration, sensor capacitance and output voltage is investigated in designing phase of the capacitive sensor. In second phase, an interface circuit compatible to designed capacitive sensor is proposed to detect capacitance changes in terms of voltage variations. The theoretical analysis and simulation are performed with dedicated software for each designing phase and validated with experimental measurements.